Zonation-based landslide hazard assessment using artificial neural networks in the China-Pakistan Economic Corridor - Jianqiang, Zhang; Yonggang, Ge; Yong, Li; Qiang, Zou; Yuhong, Jiang; Huayong, Chen; Xiaoqing, Chen (Frontiers in Earth Science, 2022)
Distribution of landslide is controlled by various causative factors that have different impacts on the occurrence of landslide in different regions. Using one single model to build the hazard assessment is not enough to fully reflect the spatial differences of landslide controlling factors especially for large area. Landslide hazard assessment based on zonation was therefore proposed in this study with an attempt to take effective measures to solve this problem. The China-Pakistan Economic Corridor (CPEC) was taken as the study area where landslide hazard assessment was carried out. Based on the features of geological structure, topography and climate, the study area was divided into three zones. The controlling factors were further analyzed by Geographical Detectors method. It was found that the main controlling factors for landslide in three zones were related to the site’s topography (altitude, slope gradient and relief amplitude), land use, and distance to an earthquake epicenter. Furthermore, different factors for landslide hazard assessment were selected based on controlling factor analysis result. An Artificial Neural Network model was utilized to build the hazard assessment models and hazard assessment maps were generated. Validations were conducted, showing that the accuracy of hazard assessment maps by zones was higher than by the whole study area despite there was no significant difference during the modeling process.